Peningkatan Pengetahuan tentang Donor Plasma Konvalesen - Marius Agung Sasmita Jati; Eva Runi Khristiani; Muryani Muryani (STIKES Wira Husada Yogyakarta, 2022)
Increased knowledge about convalescent plasma donor. Convalescent plasma donors are currently experiencing stagnation due to public ignorance about the importance of convalescent plasma donors from Covid-19 survivors. The purpose of this community service is to increase knowledge about convalescent plasma donors. Activities in the form of counseling with lectures. Submission of material with presentations and videos. Knowledge improvement was measured by pretest and posttest questionnaires. The results of the activity showed that after being given counseling the percentage of adolescents who answered correctly increased by 70% (correct score <10), 58.33% (10 correct 15), and 93.33% (correct score>15). Counseling can increase knowledge about convalent plasma donors in adolescents.